Digital Economy - This is the Economy of the Current Times - ugli, Sharobiddinov Ahrorbek Qosimjon (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
Currently, in many developed countries, the digital economy and the factors of their development have a significant impact, and the digital economy plays an important role in the life of society. The article describes the definitions and different approaches to the category of "digital economy". Also, the essence, classification, development trends, advantages and disadvantages of electronic commerce, which is part of the digital economy, are shown on the example of foreign countries. Proposals and recommendations for the development of electronic commerce in Uzbekistan have been developed.